RESTRICTION OF RIGHTS OF NON-GOVERNMENTAL ORGANIZATIONS IN RUSSIA AS A SUBJECT OF JUDICIAL CONTROL - P. Vinogradova (BRICS Law Journal)
This article examines the issue of the regulation of the Russian state’s control over the activities of non-governmental organizations and the limits to that control. Important changes made in 2014–2016 in the regulation of the organization and activity of judicial power show that the tasks of transformation of the judicial power structure, establishment of effective control mechanisms and strengthening of the requirements on substantiation of court judgments have become more topical. Addressing this issue and taking it as the subject of study are motivated by the small number of works dealing with this issue. The task of enhancing the effectiveness of the exercise of their powers by public authorities necessitates consideration of special features of judicial control over disputes related to restriction of rights. The adoption of the Administrative Procedure Code of the Russian Federation and the statutory formalization of special features of judicial control with respect to certain non-commercial organizations imply changes in judicial practice related to challenging the decisions made by public authorities. In addition to special procedural features such changes also facilitate the spread in law enforcement practice of legal arrangements like the ‘proportionality test’ and determining the balance between competing constitutional values and conditions of public order observance. The analysis carried out by the author reveals tendencies of improvement in legislative action and allows identification of future lines of improvement in judicial practice.